Topical treatment of melanoma metastases with imiquimod, plus administration of a cancer vaccine, promotes immune signatures in the metastases - Mauldin, Ileana S. (Cancer Immunol Immunother, 2016)
INTRODUCTION: Infiltration of cancers by T cells is associated with improved patient survival and response to immune therapies; however, optimal approaches to induce T cell infiltration of tumors are not known. This study was designed to assess whether topical treatment of melanoma metastases with the TLR7 agonist imiquimod plus administration of a multipeptide cancer vaccine will improve immune cell infiltration of melanoma metastases. PATIENTS AND METHODS: Eligible patients were immunized with a vaccine comprised of 12 melanoma peptides and a tetanus toxoid-derived helper peptide, and imiquimod was applied topically to metastatic tumors daily. Adverse events were recorded, and effects on the tumor microenvironment were evaluated from sequential tumor biopsies. T cell responses were assessed by IFNγ ELIspot assay and T cell tetramer staining. Patient tumors were evaluated for immune cell infiltration, cytokine and chemokine production, and gene expression. RESULTS AND CONCLUSIONS: Four eligible patients were enrolled, and administration of imiquimod and vaccination were well tolerated. Circulating T cell responses to the vaccine was detected by ex vivo ELIspot assay in 3 of 4 patients. Treatment of metastases with imiquimod induced immune cell infiltration and favorable gene signatures in the patients with circulating T cell responses. This study supports further study of topical imiquimod combined with vaccines or other immune therapies for the treatment of melanoma. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00262-016-1880-z) contains supplementary material, which is available to authorized users.